2006
DOI: 10.1139/h06-005
|View full text |Cite
|
Sign up to set email alerts
|

Is isometric strength loss immediately after eccentric exercise related to changes in indirect markers of muscle damage?

Abstract: This study tested the hypothesis that the magnitude of maximal isometric strength (MVC) loss immediately following eccentric exercise (MVC-post) would relate to changes in other indirect markers of muscle damage following exercise. Eighty-nine men were recruited from the same student population and performed 24 maximal eccentric actions of the elbow flexors. Commonly used markers of muscle damage such as relaxed and flexed elbow joint angles, range of motion (ROM), upper-arm circumference, muscle soreness, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
42
1
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 23 publications
7
42
1
7
Order By: Relevance
“…The performance of 60 eccentric actions of the elbow flexors at 90° s −1 resulted in significant decrements in isometric strength and ROM, elevated levels of palpated muscle soreness and significant increases in plasma CK activity 4 days post-exercise (fig 4A−D). The extent of subject variability recorded following isokinetic exercise is similar to the variability previously described following manually controlled eccentric exercise 14. Measures of work performed during exercise (Total work, Wk/MVC and %Δ Wk) demonstrated a significant correlation with many of the variables including ROM and SOR; however, the correlations were not strong (table 1).…”
Section: Discussionsupporting
confidence: 70%
“…The performance of 60 eccentric actions of the elbow flexors at 90° s −1 resulted in significant decrements in isometric strength and ROM, elevated levels of palpated muscle soreness and significant increases in plasma CK activity 4 days post-exercise (fig 4A−D). The extent of subject variability recorded following isokinetic exercise is similar to the variability previously described following manually controlled eccentric exercise 14. Measures of work performed during exercise (Total work, Wk/MVC and %Δ Wk) demonstrated a significant correlation with many of the variables including ROM and SOR; however, the correlations were not strong (table 1).…”
Section: Discussionsupporting
confidence: 70%
“…As the MR images provide a more complete evaluation of the extent of muscle damage compared with damage assessed from a biopsy sample, the authors suggested that the large variability in CK response is related to the variability in EIMD. In contrast, other studies (Nosaka et al, 2006;Skurvydas et al, 2011) demonstrated that reduction in strength loss poorly reflected the distribution of some measures, such as peak CK activity. In addition, it is worth noting that for the first time, the present study transformed the CK data as logarithm, allowing a linear correlation to be apparent.…”
Section: Discussionmentioning
confidence: 86%
“…We observed that subjects assigned in the HR group were those experiencing the largest absolute and relative work decrease during the eccentric exercise. The relationship between CK activity and muscle force loss immediately post‐exercise has already been investigated many times in humans (Clarkson et al., ; Nosaka & Clarkson, ; Nosaka et al., ; Skurvydas et al., ), but the findings remained equivocal and none of these studies tested the relationship between CK and the modifications of the work parameter during the exercise instead of strength loss post‐exercise. For example, Nosaka and Clarkson () previously demonstrated significant correlations of peak CK levels after isokinetic eccentric protocol with muscle strength loss post‐exercise and abnormality in magnetic resonance (MR) images.…”
Section: Discussionmentioning
confidence: 99%
“…Although histological alterations provide a direct evidence of muscle damage, eccentric exercise-induced muscle damage is often assessed indirectly by increases in muscle proteins in the blood (e.g., creatine kinase: CK), ratings of delayed onset muscle soreness, and decreases in muscle strength and range of motion (Nosaka & Clarkson, 1995;Chen et al, 2010Chen et al, , 2011. Among these, a prolonged decrease in maximum voluntary contraction (MVC) peak force or torque has been considered to be the best indirect measure of eccentric exercise-induced muscle damage (Warren et al, 1999;Nosaka et al, 2006). Large decreases in MVC peak force (30-50%) are evident for several days following maximal eccentric elbow flexor exercise, together with abnormalities shown by ultrasound and/or magnetic resonance imaging (Nosaka & Clarkson, 1996) and myofibril necrosis (Jones et al, 1986;Mackey et al, 2011).…”
mentioning
confidence: 99%